Design Options for Building a New Life in Australia: The Longitudinal Survey of Humanitarian Migrants - Gray, Matthew; Graycar, Adam; Nicoloau, Loucas (My University, 2012)
The paper discusses the key design choices, and the strengths and weaknesses of different design options for ‘Building a New Life in Australia: The Longitudinal Study of Humanitarian Migrants’. It also outlines a suggested design and architecture for the study.
Keywords: Culture -- Immigrants; Life Events -- Immigration / newly arrived migrants; Disadvantage, adversity and resilience; Culture; Life Events; Immigrants; Immigration / newly arrived migrants; Dsiadvantage, adversity and resilience; Adversity and resilience